RAPID DETECTION OF AFLATOXIGENIC PRODUCING ATRAINS OF ASPERGILLUS FLAVUS FROM POULTRY FEES BY UV LIGHT AND AMMONIA - Raed Najeeb Alkhersan; Mohammed H. Khudor; Basil A. Abbas (Basrah Journal of Veterinary Research)
A total 180 samples of pellet poultry feed were collected from poultry feed stores and localmarkets .They were cultured on potato dextrose agar(PDA) and malt extract agar (MEA) forisolation and identification of Aspergillus flavus.They were Sub-cultured on sabouraud dextroseagar(SDA) .Then the isolates were cultured on coconut agar medium(CAM) . The rapid detectionof 50 selected isolates of contaminated poultry feed samples with A.flavus were achieved by blue–green fluorescence under UV light and by ammonia vapor on CAM medium to determine theaflatoxigenic isolates of A.flavus. The detection by UV light revealed that 26 (52%) of isolateswere aflatoxigenic (positive) by produce blue-green fluorescence under UV light at 356nm , andalso 26 (52%) of isolates were aflatoxigenic (positive) by turned the colony reverse to pink colorby exposure to ammonia vapor.